The Importance of Using Collaborative Learning Strategy in Learning English Writing - Abuhabil, Sumaia; Aswese, Sana ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2018)
This study investigated the importance of using collaborative learning as a strategy to enhance English writing skills of EFL learners. The study was a classroom based, the participants of the study were 25 female Libyan students from two different secondary schools in Misrata .All students who were chosen randomly were asked to fill in the questionnaire given. The research was done by using a mixed method approach. The data analysis obtained from the questionnaire and observation indicated that the majority of students were positive about collaborative writing although some of them were not interested when engaging collaboratively .It is a suitable and applicable strategy for improving students’ English writing performance and to develop their critical thinking. Moreover, working collaboratively has a good impact on all members in a group since collaboration engages students to express their opinions and respect others’ opinions; it fosters negotiation, and it engages students to share their knowledge.